Peroxidase-Generated Apoplastic ROS Impair Cuticle Integrity and Contribute to DAMP-Elicited Defenses - Survila, Mantas; Davidsson, Pär R.; Pennanen, Ville; Kariola, Tarja; Broberg, Martin; Sipari, Nina; Heino, Pekka; Palva, Erkki T. (Frontiers in Plant Science, 2016)
Cuticular defects trigger a battery of reactions including enhanced reactive oxygen species (ROS) production and resistance to necrotrophic pathogens. However, the source of ROS generated by such impaired cuticles has remained elusive. Here, we report the characterization of Arabidopsis thaliana ohy1 mutant, a Peroxidase 57 (PER57) - overexpressing line that demonstrates enhanced defense responses that result both from increased accumulation of ROS and permeability of the leaf cuticle. The ohy1 mutant was identified in a screen of A. thaliana seedlings for oligogalacturonide (OGs) insensitive/hypersensitive mutants that exhibit altered growth retardation in response to exogenous OGs. Mutants impaired in OG sensitivity were analyzed for disease resistance/susceptibility to the necrotrophic phytopathogens Botrytis cinerea and Pectobacterium carotovorum. In the ohy1 line, the hypersensitivity to OGs was associated with resistance to the tested pathogens. This PER57 overexpressing line exhibited a significantly more permeable leaf cuticle than wild-type plants and this phenotype could be recapitulated by overexpressing other class III peroxidases. Such peroxidase overexpression was accompanied by the suppressed expression of cutin biosynthesis genes and the enhanced expression of genes associated with OG-signaling. Application of ABA completely removed ROS, restored the expression of genes associated with cuticle biosynthesis and led to decreased permeability of the leaf cuticle, and finally, abolished immunity to B. cinerea. Our work demonstrates that increased peroxidase activity increases permeability of the leaf cuticle. The loss of cuticle integrity primes plant defenses to necrotrophic pathogens via the activation of DAMP-responses.